Reconstructing the Role of Waqf in Indonesia's Islamic Financial Ecosystem: Institutional and Regulatory Analysis - Irma Suryani Lubis; Muslim Marpaung (International Journal of Management Research and Economics, 2025)
Waqf has long been a pillar of Islamic philanthropy and socio-economic development, yet its potential remains underutilized in Indonesia’s modern Islamic financial ecosystem. This article examines how waqf can be repositioned and optimized within Indonesia’s Islamic finance, focusing on institutional roles and regulatory frameworks. Adopting a qualitative approach that combines theoretical-conceptual analysis with case studies, we review Islamic legal principles, national laws, and recent innovations. We analyze three emblematic cases – L-Kaf Sidogiri (a pesantren-based waqf institution), Dompet Dhuafa (a prominent Islamic philanthropic foundation), and the Cash Waqf-Linked Sukuk (CWLS) – to illustrate successes and challenges in waqf management. Our findings reveal that while waqf is recognized as a key instrument in poverty alleviation and social welfare financing, its impact is limited by fragmented institutions, gaps in regulation, low public awareness, and governance weaknesses. However, successful models of productive waqf and financial innovation demonstrate the feasibility of an integrated waqf ecosystem. We discuss strategies to strengthen legal frameworks, enhance institutional capacity, and synergize waqf with Islamic banking, capital markets, and technology. The article offers policy recommendations toward “mainstreaming” waqf in Indonesia’s Islamic financial sector, thereby unlocking waqf’s potential for sustainable development.